Biodegradation of lignin and nicotine with white rot fungi for the delignification and detoxification of tobacco stalk - Su, Yulong (BMC Biotechnol, 2016)
BACKGROUND: Tobacco stalk is one kind of abundant crop residues in China. The high lignification of tobacco stalk increases its reusing cost and the existing of nicotine will cause serious pollution. The biodegradation of lignocellulosic biomass has been demonstrated to be an environmental and economical approach for the utilization of plant stalk. Meanwhile, many nicotine-degrading microorganisms were found in nature. However, microorganisms which could degraded both nicotine and lignin haven’t been reported. Therefore, it’s imperative to find some suitable microorganisms to break down lignin and simultaneously remove nicotine in tobacco stalk. RESULTS: The nicotine in tobacco stalk could be degraded effectively by Trametes versicolor, Trametes hirsute and Phanerochaete chrysosporium. The nicotine content in tobacco stalk was lowered to below 500 mg/kg (a safe concentration to environment) after 10 days of fermentation with Phanerochaete chrysosporium and Trametes versicolor, and 15 days with Trametes hirsute. The degradation rate of lignin in the fermented tobacco stalk was 37.70, 51.56 and 53.75% with Trametes versicolor, Trametes hirsute and Phanerochaete chrysosporium, respectively. Meanwhile, 24.28% hemicellulose was degraded by Phanerochaete chrysosporium and 28.19% cellulose was removed by Trametes hirsute. Through the enzyme activity analysis, the main and highest ligninolytic enzymes produced by Phanerochaete chrysosporium, Trametes hirsute and Trametes versicolor were lignin peroxidase (88.62 U · L(−1)), manganese peroxidase (100.95 U · L(−1)) and laccase (745.65 U · L(−1)). Meanwhile, relatively high and stable cellulase activity was also detected during the fermentation with Phanerochaete chrysosporium, and the highest endoglucanase, exoglucanase and filter paper enzyme activities were 0.38 U · mL(−1), 0.45 U · mL(−1) and 0.35U · mL(−1), respectively. Moreover, the products in the fermentation of tobacco stalk with P. chrysosporium were identified with GC-MS, besides the chemicals produced in the degradation of lignin and nicotine, some small molecular valuable chemicals and fatty acid were also detected. CONCLUSIONS: Our study developed a new method for the degradation and detoxification of tobacco stalk by fermentation with white rot fungi Phanerochaete chrysosporium and Trametes hirsute. The different oxidative enzymes and chemical products detected during the degradation indicated a possible pathway for the utilization of tobacco stalk. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12896-016-0311-8) contains supplementary material, which is available to authorized users.